Potential Use of Alginate-Based Carriers As Antifungal Delivery System - Spadari, Cristina de Castro; Lopes, Luciana B.; Ishida, Kelly (Frontiers in Microbiology, 2017)
Fungal infections have become a major public health problem, growing in number and severity in recent decades due to an increase of immuncompromised patients. The use of therapeutic agents available to treat these fungal infections is limited by their toxicity, low bioavailability, antifungal resistance and high cost of treatment. Thus, it becomes extremely important to search for new therapeutic options. The use of polymeric systems as drug carriers has emerged as a promising alternative to conventional formulations for antifungals. Alginate is a natural polymer that has been explored in the last decade for development of drug delivery systems due to its non-toxicity, biodegradability, biocompatibility, low cost, mucoadhesive and non-immunogenic properties. Several antifungal agents have been incorporated in alginate-based delivery systems, including micro and nanoparticles, with great success, displaying promising ‘in vitro” and “in vivo” results for antifungal activities, reduction in the toxicity and the total drug dose used in the treatment, and improved bioavailability. This review aims at discussing the potential use and benefits of alginate-based nanocarriers and other delivery systems containing antifungal agents in the therapy of fungal infections.